House Atreides Characters’ Impoliteness Super-Strategies and Communicative Functions in Dune - Brian Ramadhan Sono; Bramantya Pradipta; I Wayan Budiarta (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the impoliteness super-strategies and communicative functions employed by House Atreides characters in the official movie scripts of Dune: Part One (2021) and Dune: Part Two (2024), using Culpeper’s (1996, 2011) impoliteness framework. A qualitative descriptive approach was adopted, with the official scripts as the sole data source; utterances containing face-threatening acts were identified through repeated close reading, coded, and classified according to Culpeper’s (1996) five impoliteness super-strategies and Culpeper’s (2011) three communicative functions. The findings show that House Atreides characters employ four of the five super-strategies, Bald on Record, Positive, Negative, and Sarcasm/Mock Impoliteness, while Withholding Politeness does not occur; Bald on Record Impoliteness is the most frequent, reflecting the characters’ militaristic and authoritative social roles. Regarding communicative function, coercive impoliteness predominates, followed by affective impoliteness, while entertaining impoliteness occurs only among characters bound by close personal trust. These results indicate that impoliteness operates as a deliberate linguistic resource through which nominally honourable characters negotiate authority, vent emotional strain, and, within intimate relationships, build solidarity through banter. The study extends Culpeper’s model to scripted science-fiction political discourse and suggests that a full account of institutional impoliteness requires supplementing Culpeper’s taxonomy with power-based perspectives such as Bousfield and Locher (2008). The findings offer a reference point for future pragmatic research on impoliteness, power, and characterization in cinematic narrative.